Peer-Mentored Community Reentry Reduces Recidivism - Sells, Dave (Criminal justice and behavior, 2020)
Most people released from incarceration in the criminal justice system return to prison within 3 years. To improve community reentry, national initiatives have promoted new and revitalized programming, including peer mentorship, though this approach remains largely unstudied. Fifty-five men participated within a pilot randomized controlled trial investigating the effect of peer mentorship upon recidivism. Hierarchical binary logistic regression including recidivism risk, as well as group assignment to either a standard services for community reentry condition or standard services plus peer mentorship condition, showed that those receiving mentorship had significantly lower recidivism. It appears that peer mentorship with a model focus upon early intervention, relationship quality, criminal desistance, social navigation, and gainful citizenship may promote the complex task of early community reentry. Given this pilot’s small sample, future research should confirm this association on a larger scale, enabling longitudinal and treatment component analyses examining the relative contributions of mentorship model factors.